Anxiety and Depression among Patients with Chronic Obstructive Pulmonary Disease - Acharya, Chandra Prakash; Poudel, Kalpana; Thapaliya, Rekha (Nepal Journal of Medical Sciences, 2020)
Introduction: The prevalence of anxiety and depression among patients with COPD is significantly higher than the general population; there are serious barriers to the recognition and treatment of these co-morbid conditions. The study aimed to identify the anxiety and depression among patients with COPD. Methods: A cross sectional study design was adopted and consecutive sampling technique was used to collect 131 samples. A structured interview schedule of Beck Depression Inventory and Beck Anxiety Inventory was used. Results: Low level of anxiety was found among 83(63.4%) of COPD patients whereas 16(12.3%) had potentially concerning levels of anxiety. It also reveals that 31(23.7%) of the COPD patients were suffering from moderate depression, 14(10.7%) had severe depression whereas 7(5.3%) had extreme depression. A total of 28(21.4%) of them were free from depression. There was association between alcohol consumption and depression (p=0.00). Likewise, there was association between age (p=0.03), educational status (p=0.04), types of family (p=0.00), smoking habit (p=0.01), duration of disease diagnosed (p=0.01) and duration of treatment (p=0.00) with anxiety. Conclusions: It is concluded that one fourth of the COPD patients had moderate level of anxiety as well as depression. Additionally, some of the COPD patients also suffered from extreme depression.